Financial Protection of Critical Infrastructure Services - World Bank (World Bank, Washington, DC, 2022)
This report uses the term critical infrastructure to refer to all the aspects required to deliver the critical services (e.g., transport, health care, energy). Six sectors are widely classified as being critical: energy, transport, water, information and communications technologies, health care, and finance. Some economies include education and critical economic and manufacturing sectors within their definitions. The focus of this report is on the financial protection of critical infrastructure services. This focus complements existing, well-documented evidence and frameworks, including evidence collated by the World Bank30, about the operational and physical protection and the resilience of critical infrastructure assets, and about best practice in incorporating resilience within PPPs in infrastructure. The financial aspects of resilience of critical infrastructure services are not widely discussed in the existing literature, yet this is a critical component of overall resilience. A 2014 publication by the Organization for Economic Co-operation and Development (OECD) titled Recommendations on Managing Critical Risks emphasized the role of financial preparedness in managing critical infrastructure risks to protect public finances and the fiscal position of a country. The 2018 and 2019 APEC Joint Ministerial Statements explicitly highlight the importance of quality and resilience, of the infrastructure’s strengths against climate and disasters, and of the role of financial protection in this context.